2010
DOI: 10.1507/endocrj.k09e-332
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Functions of GPR30/GPER-1, a Membrane Receptor for Estrogen: From Discovery to Functions In Vivo

Abstract: Summary. G protein-coupled receptor 30/G protein-coupled estrogen receptor-1 (GPR30/GPER-1) was reported as a novel membrane receptor for estrogen in 2005. However, the research on GPR30 has produced conflicting reports with regard to its intracellular localization, the tissue distribution of its expression, and some its functions. Recently, in addition to the finding of G-1, a GPR30 agonist, GPR30 KO mice have been produced in laboratories, and this has significantly increased the confidence in the data. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 31 publications
2
58
0
1
Order By: Relevance
“…Moreover, the two mutually supportive lines of evidence presented here also support the suggestion that both endogenous and recombinant GPR30 protein can exist at the plasma membrane (18,96); first, by isolated plasma membrane preparations from the rat hippocampus in vivo and, second, by the biotinylation of surface proteins in vitro. Previous confocal microscopy studies on cultured cells have questioned the localization of GPR30 at the plasma membrane (97,98), but the evidence demonstrated here would suggest that GPR30 protein indeed can be localized at the plasma membrane.…”
Section: Psd-95 Interaction Functions To Increase the Amount Of Gpr30supporting
confidence: 83%
“…Moreover, the two mutually supportive lines of evidence presented here also support the suggestion that both endogenous and recombinant GPR30 protein can exist at the plasma membrane (18,96); first, by isolated plasma membrane preparations from the rat hippocampus in vivo and, second, by the biotinylation of surface proteins in vitro. Previous confocal microscopy studies on cultured cells have questioned the localization of GPR30 at the plasma membrane (97,98), but the evidence demonstrated here would suggest that GPR30 protein indeed can be localized at the plasma membrane.…”
Section: Psd-95 Interaction Functions To Increase the Amount Of Gpr30supporting
confidence: 83%
“…In this respect, the recent identification of molecules acting as selective agonist or antagonist ligands of GPER1 has allowed the evaluation of the transduction mechanisms involved in the estrogenic GPER1 signaling in numerous pathophysiological conditions (Dennis et al 2011. Indeed, GPER1 has been implicated not only in cancer, but also in cardiovascular, immunological, and neurological functions as well as diabetes (Mizukami 2010). GPER1 has been proposed as an interesting therapeutic target in diabetes and pancreatic islet transplantation (Mårtensson et al 2009, Liu et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have revealed that estrogen may mediate fast signal responses or transcriptional events via G protein-coupled estrogen receptor 1 (GPER1) (13). GPER1 is expressed in human brain, liver, heart, kidney, pancreatic, placental, blood vessel, bone, lymphoid, endometrial, ovarian, breast and lung cancer tissues (14). This receptor may be localized on the cell membrane, nucleus, endoplasmic reticulum, mitochondria or Golgi apparatus, and its effects vary depending on this specific intracellular localization (14).…”
Section: Introductionmentioning
confidence: 99%
“…GPER1 is expressed in human brain, liver, heart, kidney, pancreatic, placental, blood vessel, bone, lymphoid, endometrial, ovarian, breast and lung cancer tissues (14). This receptor may be localized on the cell membrane, nucleus, endoplasmic reticulum, mitochondria or Golgi apparatus, and its effects vary depending on this specific intracellular localization (14). It has been suggested that G-1 (chemical name, 1-[4-(6-bromo-1,3-benzodioxol-5-yl)-3a,4,5,9b-tetrahydro-3H-cyclopenta[c]quinolin-8-yl]-ethanone) acts a specific GPER1 agonist (15).…”
Section: Introductionmentioning
confidence: 99%